Products of lipid, protein and RNA oxidation as signals and regulators of gene expression in plants - Chmielowska-Bąk, Jagna; Izbiańska, Karolina; Deckert, Joanna (Frontiers in Plant Science, 2015)
Reactive oxygen species (ROS) are engaged in several processes essential for normal cell functioning, such as differentiation, anti-microbial defense, stimulus sensing and signaling. Interestingly, recent studies imply that cellular signal transduction and gene regulation are mediated not only directly by ROS but also by the molecules derived from ROS-mediated oxidation. Lipid peroxidation leads to non-enzymatic formation of oxylipins. These molecules were shown to modulate expression of signaling associated genes including genes encoding phosphatases, kinases and transcription factors. Oxidized peptides derived from protein oxidation might be engaged in organelle-specific ROS signaling. In turn, oxidation of particular mRNAs leads to decrease in the level of encoded proteins and thus, contributes to the post-transcriptional regulation of gene expression. Present mini review summarizes latest findings concerning involvement of products of lipid, protein and RNA oxidation in signal transduction and gene regulation.